Writing with style : - Trimble, John R. (Prentice Hall, 1975)
A storehouse of practical writing tips, written in a lively, conversational style. Readers lean to develop a “writer's sense” : the book demonstrates that writing is really applied psychology since it is essentially the art of creating desired effects. Provides an explanation of what effects are desirable and how to create them. An exceptional book that works successfully on several levels simultaneously. Provides new insight into: how to generate interesting ideas and get them down on paper; how to write a critical analysis; how to write a crisp opener; how to invigorate a banal style; how to punctuate with confidence; how to handle various conventions, and much more. For anyone who needs a reference guide on writing